Male Shadowing: The Lingering Phantom of Patriarchal Society as Seen in The Glass Menagerie - Deta Maria Sri Darta (Universitas Stikubank (UNISBANK) Semarang, 2013)
Living in patriarchal society makes women have tostruggle hard to be heard. This is because everything is determined by malestandard, including what is appropriate or not. When women find a way tovocalize their thought, we have to chew this a little bit. We need toreconsider whether women’s voice are really appreciated or women have become atool or hand extension for men to rule the world. This article would like tosee how a strong woman as representated by Amanda tends to preserve the idea ofmale oriented in The Glass Menagerie.The discussion shows that although it is shown that Amanda is able to act asthe head of her family to replace her husband, her strong will is beingmis-used by the patriarchal system to educate her children according to systemvalues. It demonstrates that men shadow has become a lingering panthom forwomen in their movements toward liberty.Keywords: male shadowing, patriarchalsociety, The Glass Menagerie